Examining the relationship between financial performance indicators and capitalization ratios: Analysis of Ghana's banking sector - Owusu, Caleb Kwasi; Garr, David Kwashie (International Journal of Financial, Accounting, and Management, 2024)
Purpose: This study examines the relationship between the capitalization ratio and business profitability, particularly its effect on return on assets (ROA) and return on equity (ROE). Capitalisation is crucial for financial growth and operational stability; however, an imbalance in the capital structure can adversely affect profitability. This study examines the essential issue of optimising capitalisation to improve firm performance, particularly under fluctuating economic conditions. Method: This study employs a quantitative research approach to analyse firm-level data and to examine the relationship between capitalisation and profitability, with E-veiw as the analytical tools for regression analysis. The results indicate that elevated capitalisation ratios correlate with diminishing profitability and lower equity returns, highlighting the danger of excessive leverage. Overreliance on debt financing increases financial and operational risks, restricts liquidity, and reduces shareholders’ net returns. Results: This research provides practical recommendations for corporate executives and governments. Businesses are urged to use balanced capital structures to improve financial flexibility and secure sustainable returns. Policymakers must strengthen regulatory frameworks to promote prudent financial management and mitigate the dangers linked to excessive debt financing. Contribution: This study contributes to the literature by offering empirical information regarding the relationship between capitalization and profitability, specifically in emerging markets. The work's novelty is in its concrete advice that links academic frameworks to practical financial strategies.